Facile Solution Synthesis, Processing and Characterization of n- and p-Type Binary and Ternary Bi–Sb Tellurides - Bejan Hamawandi; Sedat Ballikaya; Hazal Batili; Viking Roosmark; Martina Orlovská; Aminu Yusuf; Mats Johnsson; Rafal Szukiewicz; Maciej Kuchowicz; Muhammet S. Toprak (Applied Sciences, 2020)
The solution synthesis route as a scalable bottom-up synthetic method possesses significant advantages for synthesizing nanostructured bulk thermoelectric (TE) materials with improved performance. Tuning the composition of the materials directly in the solution, without needing any further processing, is important for adjusting the dominant carrier type. Here, we report a very rapid (2 min) and high yield (>8 g/batch) synthetic method using microwave-assisted heating, for the controlled growth of Bi2−xSbxTe3 (x: 0−2) nanoplatelets. Resultant materials exhibit a high crystallinity and phase purity, as characterized by XRD, and platelet morphology, as revealed by SEM. Surface chemistry of as-made materials showed a mixture of metallic and oxide phases, as evidenced by XPS. Zeta-potential analysis exhibited a systematic change of isoelectric point as a function of the material composition. As-made materials were directly sintered into pellets by using spark plasma sintering process. TE performance of Bi2−xSbxTe3 pellets were studied, where the highest ZT values of 1.04 (at 440 K) for Bi2Te3 and 1.37 (at 523 K) for Sb2Te3 were obtained, as n- and p-type TE materials. The presented microwave-assisted synthesis method is energy effective, a truly scalable and reproducible method, paving the way for large scale production and implementation of towards large-area TE applications.